Predictor Variables of Mental Health in Spanish University Students - Amalia Rodríguez-Rodríguez; Eloísa Guerrero-Barona; Maria José Chambel; Mónica Guerrero-Molina; Pablo González-Rico (MDPI AG, 2022)
There is currently great concern over the increase in the cases of university students with mental health problems as the numbers have doubled over recent years. Nevertheless, there is also total agreement concerning the relationship between positive psychological variables and mental health. The objective of this study was to know the relationship between the risk of mental health disorders and the variables of gender, affects, academic engagement, satisfaction with life, health perception and the perception of happiness, as well as predict the risk of suffering mental health disorders. The sample comprised 461 students from the Science Faculty of the University of Extremadura (Spain), of whom 50.3% were women. We used the General Health Questionnaire (GHQ12) to assess mental health, The results indicate that 65.6% of the students showed a risk of suffering from mental health disorders. A greater number of negative affect is related to a greater risk of suffering mental health disorders; while the perception of both health and happiness are related to a lower risk. Similarly, it should be said that the results demonstrate that being a woman increases the risk of suffering mental health disorders by 63.7%.